Loss of natural coastline influences species diversity of anemonefish and host anemones in the Ryukyu Archipelago - Hayashi, Kina; Tachihara, Katsunori; Reimer, James Davis (Aquatic conservation, 2021)
Anemonefish and host anemones are distributed in the shallow waters of coral reefs, and thus their existence may be affected by coastal development. The Ryukyu Archipelago includes the Okinawa and Sakishima Islands; the former has experienced extensive land reclamation and drainage in coastal areas while the latter still mostly contains natural coasts. To consider the layout of protected areas needed to conserve diversity of host anemones and anemonefish in the Ryukyu Archipelago, the community structure and coexistence mechanisms of anemones and anemonefish were compared between Okinawa and Sakishima Islands. Six species of anemonefish and seven species of host anemone are distributed in both islands. Among 15 species‐pair interactions observed in six species of anemonefish in the Sakishima Islands, 14 were explained by the niche differentiation hypothesis and only one interaction was explained by the cohabitation hypothesis. In the Okinawa Islands, 13 interactions were explained by the niche differentiation hypothesis, one by the cohabitation hypothesis and one by the lottery hypothesis. For both host anemones and anemonefish, β‐diversity in the Okinawa Islands was lower and had a more nested structure than that of the Sakishima Islands. β‐Diversity and its nestedness did not differ between the two regions excluding study sites adjacent to coastlines, suggesting that differences in the coastal environment affected the diversity of anemones and anemonefish in the Ryukyu Archipelago. These results suggested that there is an urgent need to prioritize the conservation of reef edges, where species diversity is relatively higher than directly next to the terrestrial coastline in Okinawa Island. In the Sakishima Islands, where many natural coasts remain, a wider area from directly next to the coast out to the reef edge needs to be comprehensively protected to increase β‐diversity.